Analisis Relevansi Pembelajaran Akidah Akhlak dalam Pembinaan Akhlak Siswa di MTsN 2 Lima Puluh Kota - Halimah Tusa'diah; Arman Husni (Lembaga Yasin AlSys, 2026)
Although Akidah Akhlak learning has been widely studied, research specifically analyzing its relevance to students’ moral development in madrasahs, particularly at MTsN 2 Lima Puluh Kota, remains limited. This issue is important to examine because some students continue to display behaviors that do not reflect noble moral character, such as a lack of courtesy, discipline, and respect for teachers, indicating a gap between their understanding of the subject matter and its application in daily life. This study aims to analyze the relevance of Akidah Akhlak learning to students’ moral development and identify the challenges teachers face in its implementation. This study employed a qualitative approach with a descriptive field research design. The research informants included an Akidah Akhlak teacher as the key informant and the madrasah principal and eighth-grade students as supporting informants, who were selected purposively. Data were collected through observation, interviews, and documentation and were subsequently analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings show that Akidah Akhlak learning is highly relevant to students’ moral development because it is oriented not only toward conceptual mastery but also toward practical implementation through habituation, exemplary conduct, discussions, lectures, question-and-answer activities, and contextual examples. This relevance is reflected in increased awareness of worship and prayer as forms of moral conduct toward Allah SWT., respectful and courteous attitudes toward teachers, mutual respect and cooperation among peers, and concern for the cleanliness and orderliness of the school environment. However, students’ moral development continues to face challenges arising from mobile phone and social media use, peer influence, extensive exposure to the digital world, and insufficient supervision outside school. This study concludes that Akidah Akhlak learning is relevant to students’ moral development when supported by teachers’ exemplary conduct, continuous habituation, and synergy among the madrasah, family, and community. These findings contribute to the development of Islamic education and can provide a foundation for madrasahs to strengthen strategies for students’ moral development in the digital era.